Achieving Bangladesh's tourism potential: Linkages to export diversification, employment generation and the "green economy" - Dale Honeck; Md. Shoaib Akhtar (World Trade Organization (WTO), 2014)
Bangladesh's international image is not as a popular tourism destination, and many people might be surprised to learn it has three World Heritage sites, including the Sundarbans tiger reserves. Moreover, it is part of important travel circuits for cultural and religious tourism, and has demonstrated potential for sports tourism. The objective of this working paper is to critically test the assertion that pro-poor "green" tourism is one of the best development options for the majority of least developed countries (LDCs) - a challenging task in Bangladesh in the face of the country's success as an exporter of readymade garments - by comparing tourism to the available alternatives with regard to the crucial government priorities of export diversification, employment generation and the "green economy". It is well-known that Bangladesh is under strong pressure to diversify its exports, to generate new employment (especially in rural areas), and to respond to critical environmental issues. The government has identified over 30 "thrust sectors" (including tourism) to help address these challenges, but otherwise tourism is rarely mentioned as a major trade and development option for Bangladesh. Within the limitations of data availability, this working paper reaches the conclusion that greater efforts to develop "green" tourism would be highly beneficial for facilitating rural development, environmental and cultural protection, gender equality, and export diversification in services. The most obvious current impediments are inadequate infrastructure, lack of investment and (typically election year) political conflict, but behind these factors appear to be a serious lack of stakeholder coordination, insufficient regulatory and administrative transparency and coherence, as well as some government reluctance to relinquish greater commercial autonomy in tourism to the private sector. This paper offers extensive analysis and some suggestions to help address the impediments, including the recommendation to create a Bangladesh Tourism Stakeholders Forum.
Keywords: F13; F18; F63; H54; H77; I38; J16; J21; J24; L52; L83; O14; O15; O19; O24; P45; Q26; Q54; Q56; 330; Bangladesh; LDCs; Export Diversification; Spatial Diversification; Rural Development; Comparative Advantage; Employment Generation; Green Economy; Green Tourism; Pro-poor Tourism; Tourism Linkages; Cluster Analysis; Value Chain Analysis; Poverty Alleviation; MDGs; Gender Issues; FDI; GATS; Istanbul Programme of Action (IPoA); Rio+20